2015
DOI: 10.1007/s10967-014-3892-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear reactions and physical models for neutron activation analysis

Abstract: Neutron activation analysis, especially in its k 0 standardization is fairly robust down to the level of accuracy of a few percent, but further improvement is riddled with difficulties, i.e. multiple physical effects having opposite influences and introducing bias and uncertainty in the measured results. It is the aim of this paper to give a comprehensive review of the physical models in k 0 -NAA, by providing exact definitions of the physical quantities, detailing the procedures used for the determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…It can also be observed that It can be seen that the peak of the Maxwellian‐spectrum is at about 6.246E‐01 and 6.256E‐01 eV, respectively. The shape beyond the Maxwellian 28 is a typical (1/E) shape with dips at major resonances of 232 Th and 238 U. Also, the average flux was generated from simulation using ENDF/B VIII.0 data library was normalized and flux per unit lethargy has been plotted, as shown in Figure 4B.…”
Section: Resultsmentioning
confidence: 99%
“…It can also be observed that It can be seen that the peak of the Maxwellian‐spectrum is at about 6.246E‐01 and 6.256E‐01 eV, respectively. The shape beyond the Maxwellian 28 is a typical (1/E) shape with dips at major resonances of 232 Th and 238 U. Also, the average flux was generated from simulation using ENDF/B VIII.0 data library was normalized and flux per unit lethargy has been plotted, as shown in Figure 4B.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the shape of the (n, γ ) cross section of cadmium, the transmission characteristics of a cadmium shield can be described in good approximation by a step function, whereby neutrons below the cadmium cut-off energy E Cd (thermal neutrons) are considered as completely absorbed, while neutrons with energy above E Cd (epithermal and fast neutrons) are fully transmitted. The exact value of E Cd depends on the particular geometry and wall thickness of the cadmium case [38]. The value of E Cd = 0.55 eV is typically used and was adopted in our experiment.…”
Section: Thermal-neutron Cross Section and Resonance Integral Calcmentioning
confidence: 99%
“…This is corrected by the cadmium transmission factor F Cd , defined as the ratio between the epithermalactivation rates with and without the cadmium shield. F Cd differs from unity only for a small number of nuclides [38] and because no values of F Cd were found in the literature for the relevant reactions 53 Mn(n, γ ) and 59 Co(n, γ ), during the data evaluation it was assumed to be F Cd = 1 and thus R epi ≈R epi .…”
Section: Thermal-neutron Cross Section and Resonance Integral Calcmentioning
confidence: 99%
“…Small Angle Neutron Scatter(SANS), Ultra Small Angle Neutron Scattering(USANS) and Spin Echo Small Angle Neutron Scattering(SESAME) have been developed to probe large scale structures of various samples by measuring small angle scattering precisely. How to obtain more UCN is important in fundamental science, practical engineering, and industrial applications 11 12 13 14 15 16 , etc. Slowing down neutrons effectively is the key problem since the day when neutron was discovered.…”
mentioning
confidence: 99%